2016
DOI: 10.1007/s10237-016-0813-2
|View full text |Cite
|
Sign up to set email alerts
|

Creep and stress relaxation of human red cell membrane

Abstract: In contrast to most mechanical properties of the red cell, experimental information on stress relaxation (SR) of the membrane skeleton is scarce. On the other hand, many postulates or assumptions as to the value of the characteristic time of SR [Formula: see text] can be found in the literature. Here, an experiment is presented that allows measurement of [Formula: see text] up to values of about 10 h. The membrane skeleton was deformed passively by changing the spontaneous curvature of the bilayer thus transfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…On the other hand, an extremely slow shape recovery with a much longer characteristic time window τ ex-slow ~1000 s was also observed after the extensive diametrical aspiration of a cell for 10–100 min 3 . Such an extremely slow process was also found in segregated distribution of lipids, cytoskeleton, and mobile transmembrane proteins under micropipette suction ( τ > 30 min 46 ), existence of “memory” of lateral membrane compositions after applied shear force ( τ > 4 h 47 ), and spontaneous shape transition between discocytes and echinocytes ( τ > 10 h 48 ), but there have been no systematic investigations on the mechanism of the extremely slow phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an extremely slow shape recovery with a much longer characteristic time window τ ex-slow ~1000 s was also observed after the extensive diametrical aspiration of a cell for 10–100 min 3 . Such an extremely slow process was also found in segregated distribution of lipids, cytoskeleton, and mobile transmembrane proteins under micropipette suction ( τ > 30 min 46 ), existence of “memory” of lateral membrane compositions after applied shear force ( τ > 4 h 47 ), and spontaneous shape transition between discocytes and echinocytes ( τ > 10 h 48 ), but there have been no systematic investigations on the mechanism of the extremely slow phenomena.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of remodeling is not yet well-characterized; Ungewickell and Gratzer report that the timescale is of the order of 10 minutes for a red cell at rest [ 42 ] and Fischer reports a stress relaxation timescale ≳ 10 hours [ 43 ], while others have reported a more rapid, highly shear-dependent remodeling in red cell ghosts with significant implications for the red cell’s deformability [ 7 , 44 ]. It has been suggested that hemoglobin may stabilize the cytoskeleton, which could explain the faster remodeling observed in red cell ghosts [ 43 ], but there is no consensus in the literature on the reason for the discrepancy in remodeling timescales. To examine the hypothesis that network dynamics plays a key mechanical role, we test the effect of network dynamics on our model by incorporating rate constants k on and k off for edge formation and breakage, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We used a relatively fast disassociation constant of at least k off = 10s −1 , based on the rapid remodeling that was previously reported [ 7 , 44 ]. However, recent measurements suggest that the stress relaxation timescale is at least 10 hours [ 43 ], indicating that the true rate of remodeling is significantly slower than the value of k off = 10s −1 used for our modeling. Any potential protective effect of dynamics may therefore only be significant on the timescale of hours to days, over which cells undergo hundreds to thousands of deformation cycles.…”
Section: Discussionmentioning
confidence: 96%
“…The effect of the reference curvature on the shape of vesicles and cells has been intensively studied (Seifert et al. 1991; Fischer 2017). Especially, for the Rayleigh–Plateau instability a non-zero reference curvature has been used to explain the effect of anchoring proteins (Tsafrir et al.…”
Section: Bending Elasticity Restricts Anisotropic Rayleigh–plateau Inmentioning
confidence: 99%
“…For a membrane made of lipid molecules both the shape and the mixture of the lipids determines the reference curvature (Burger 2000;Fuller & Rand 2001;Dimova 2019). The effect of the reference curvature on the shape of vesicles and cells has been intensively studied (Seifert et al 1991;Fischer 2017). Especially, for the Rayleigh-Plateau instability a non-zero reference curvature has been used to explain the effect of anchoring proteins (Tsafrir et al 2001;Campelo & Hernández-Machado 2007).…”
Section: Influence Of Reference Curvaturementioning
confidence: 99%